1989
DOI: 10.1152/ajprenal.1989.256.2.f329
|View full text |Cite
|
Sign up to set email alerts
|

Reversible downregulation of thiazide diuretic receptors by acute renal ischemia

Abstract: Receptors for thiazide diuretic drugs in the rat renal cortex have recently been identified through the binding of [3H]metolazone, a potent diuretic with a thiazide-like mechanism of action. The present studies describe the rapid and reversible alterations that occur in thiazide receptors following acute renal ischemia in the rat. The apparent density of thiazide receptors in kidney membranes as measured by the binding of [3H]metolazone was reduced by 90% following 10 min of renal ischemia produced by clamping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Thiazide receptor density is rapidly and reversibly down-regulated by renal ischemia of short duration (10 minutes), suggesting the presence of active intracellular regulatory mechanisms such as phosphorylatioddephosphorylation (28). The results of the present study, in which thiazide receptor density was significantly lower in male than in female rats, indicate that thiazide receptors may be hormonally-regulated.…”
Section: T H I a Z I D E D I U R E T I C Receptors I N Hypertensive Ratssupporting
confidence: 42%
“…Thiazide receptor density is rapidly and reversibly down-regulated by renal ischemia of short duration (10 minutes), suggesting the presence of active intracellular regulatory mechanisms such as phosphorylatioddephosphorylation (28). The results of the present study, in which thiazide receptor density was significantly lower in male than in female rats, indicate that thiazide receptors may be hormonally-regulated.…”
Section: T H I a Z I D E D I U R E T I C Receptors I N Hypertensive Ratssupporting
confidence: 42%
“…Recently, a tilapia ortholog of zNCC-like 2, tNCC-like, was reported to be expressed in apical membranes of the tilapia skin/gill epithelia with a specific homologous antibody (17,21,29). In the Xenopus oocytes that overexpressed rat and winter flounder NCCs, the inhibitory effect of metolazone (an NCC-specific inhibitor) was examined in terms of Na ϩ influx (2). In the present in vivo study, metolazone was found to inhibit both Na ϩ and Cl Ϫ influxes in 5-dpf zebrafish embryos, the skin ionocytes of which express zncc-like 2.…”
Section: Discussionmentioning
confidence: 99%
“…E) ISCHEMIA. Beaumont et al (12) noted that warm ischemia reduced the number of [ 3 H]metolazone binding sites in rat kidney cortex. As little as 10 min of warm ischemia was sufficient to reduce the number of receptors significantly, and 30 min reduced them close to background.…”
Section: Regulation Of Na ϩ and CL ϫ Transportmentioning
confidence: 99%